The essentials of assessment literacy: Contrasts between testers and users. (July 2013) - Malone, Margaret E
Language assessment literacy refers to language instructors' familiarity with testing definitions and the application of this knowledge to classroom practices in general and specifically to issues related to assessing language. While it is widely agreed that classroom teachers need to assess student progress, many teachers and other test users have a limited understanding of assessment fundamentals. To help meet this need, a tutorial for foreign language instructors was developed (CAL, 2009) to describe the basics of language assessment and assist with test selection. In this project, group interviews and surveys were used to elicit feedback from two groups of experts, US language instructors ( N = 44) and language testers ( N = 30), on the content of the tutorial. The results of the project revealed the challenges of including the technical information considered essential by testers while meeting the real and practical needs of teachers. This paper investigates efforts to elicit language testers' beliefs about measurement basics compared with those of language educators and suggests that expert beliefs about what is essential to include in such materials differ depending on the expert perspective.